2021
DOI: 10.3389/fcimb.2021.548613
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cystic Fibrosis Airway Microbiome in Response to CFTR Modulator Therapy

Abstract: The development of CFTR modulator therapies significantly changed the treatment scheme of people with cystic fibrosis. However, CFTR modulator therapy is still a life-long treatment, which is not able to correct the genetic defect and cure the disease. Therefore, it becomes crucial to understand the effects of such modulation of CFTR function on the airway physiology, especially on airway infections and inflammation that are currently the major life-limiting factors in people with cystic fibrosis. In this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 59 publications
0
29
0
3
Order By: Relevance
“…[162]. In addition to the direct influence of CFTR functionality on parameters such as salinity [163], the composition of the oropharyngeal bacterial community is also related to the CFTR genotype [164], with possible downstream effects on antibiotic activity. Furthermore, the prescription of CFTR modulators fully depends on the CFTR genotype of patients, and CFTR modulators have been shown to interfere with antibiotic activity.…”
Section: Mediators Of the Immune Responsementioning
confidence: 99%
“…[162]. In addition to the direct influence of CFTR functionality on parameters such as salinity [163], the composition of the oropharyngeal bacterial community is also related to the CFTR genotype [164], with possible downstream effects on antibiotic activity. Furthermore, the prescription of CFTR modulators fully depends on the CFTR genotype of patients, and CFTR modulators have been shown to interfere with antibiotic activity.…”
Section: Mediators Of the Immune Responsementioning
confidence: 99%
“…In addition to this, while the study assesses the role cough swabs might have in patients treated with CFTR modulators the data was collected from patients in a pre-modulator era. While, the number of studies investigating the impact of highly effective modulators on the airway microbiome is limited, the majority indicate that CFTR modulators may alter the airway microbiome, restoring a degree of eubiosis [ 38 ]. According to the adapted island model [ 35 ] such changes could theoretically protect the microbiota from bacterial overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Highly effective CFTR modulator drugs have significantly improved outcomes in pwCF; however, in a few recent studies, they have been shown to have either no effect or a modest effect on the number of P. aeruginosa in the CF lungs (10, 67). Thus, new approaches are needed to reduce the bacterial load in the lungs of chronically colonized pwCF.…”
Section: Discussionmentioning
confidence: 99%
“…Highly effective CFTR modulator drugs have significantly improved outcomes in pwCF; however, in a few recent studies, they have been shown to have either no effect or a modest effect on the P. aeruginosa burden in the CF lungs (Davies and Martin, 2018;Yi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%